E-097 Technical outcomes of mechanical thrombectomy using the sofia plus aspiration catheter. (4th August 2020) - Witek, A; Patterson, T; Sheikhi, L; Bain, M; Hussain, M; Toth, G
Abstract : Introduction: The Sofia Plus aspiration catheter (Microvention; Tustin, CA) is a recently introduced 0.070-inch inner diameter catheter designed to provide distal intracranial access and engage thrombus to facilitate thrombectomy for acute ischemic stroke. Methods: This single-center retrospective study assessed technical outcomes of mechanical thrombectomy using the Sofia Plus aspiration catheter. Utilizing a prospective database of all acute stroke interventions at our institution, cases utilizing SOFIA Plus on the first pass were identified. Patient characteristics, procedural details, and radiographic outcomes were analyzed. Results: Sofia Plus was utilized as a first pass aspiration catheter in 138 cases. Patients presented with a median NIHSS of 17 (IQR 10–22), ASPECT of 10 (IQR 8–10), and had target occlusions involving the ICA (n=30), M1 (n=73), M2 (n=22), or basilar artery (n=13). The aspiration catheter was used for first-pass direct aspiration alone in 86 patients (62%), and in conjunction with a stent retriever in 52 patients (38%). A recanalization grade of TICI 2b or better was achieved in 118 patients (86%), which was accomplished with a single pass in 88 (64%). Median time from groin puncture to recanalization was 44 minutes (IQR 30–68). Comparison of direct aspiration alone versus with stent retrievers demonstrated no difference in recanalization grade (p=0.64) or rates of first-pass recanalization (p=0.28), but direct aspiration was associated with faster recanalization (41 vs 53 minutes, p=0.02). There were two cases of vessel perforation (both involving stent retrievers), and two additional patients had symptomatic ICH on follow-up CT. Conclusions: Our experience demonstrates that the SOFIA Plus aspiration can facilitate safe and effective revascularization for acute ischemic stroke, either using a direct aspiration technique or in conjunction with a stent-retriever. However, reperfusion was achieved faster with direct aspiration alone. Disclosures: A. Witek: None. T. Patterson: None. L. Sheikhi: None. M. Bain: 2; C; Medtronic PLC, Stryker Corp. M. Hussain: 2; C; Johnson & Johnson. G. Toth: None.